2020
DOI: 10.1088/1757-899x/989/1/012024
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on corrosion initiative of infused reinforcing bar in concrete

Abstract: Durability of concrete is the essential property for the lifespan of concrete structures. Rusting of steel is the major factor responsible for the loss of durability property. In order to study the corrosion behaviour of three types of reinforcing bars like Thermo-mechanically treated bar(TMT), Corrosion resistant steel (CRS), Epoxy coated rebar(ECR) were experimentally studied. The reinforcing bars having 12 mm diameter were infused in 300×300×75 mm size of concrete slab samples were kept under room temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The thermal insulating capabilities of FC are second to none. When the thermal characteristics of foam concrete with the targeted density of 1000kg/cm 3 was compared to those of cement-sand mortar, it is confirmed that the foam concrete are six times better than those of cement-sand mortar [25,26]. The waste material of silica fume is an inanimate by-product that is obtained from the metallurgical sector [15][16][17][18].…”
Section: Introductionmentioning
confidence: 91%
“…The thermal insulating capabilities of FC are second to none. When the thermal characteristics of foam concrete with the targeted density of 1000kg/cm 3 was compared to those of cement-sand mortar, it is confirmed that the foam concrete are six times better than those of cement-sand mortar [25,26]. The waste material of silica fume is an inanimate by-product that is obtained from the metallurgical sector [15][16][17][18].…”
Section: Introductionmentioning
confidence: 91%
“…4 shows that the physical properties of Monofilament Polypropylene Fiber. These values are collected by purchasing place of the material.…”
mentioning
confidence: 99%